ANALISIS KESULITAN BELAJAR SISWA KELAS IV SD NEGERI MERBAUN KABUPATEN KUPANG - Markus Sampe; Silvester P Taneo; Falensia R Bunga (Journal of Character and ELementary Education, 2023)
The purposes of this study were (1) to find out what learning difficulties were experienced by fourth-grade students at SD Negeri Merbaun, Kupang Regency, (2) to find out what factors influenced learning difficulties for fourth-grade students at SD Negeri Merbaun, Kupang Regency, and (3) to find out how to overcome learning difficulties for fourth-grade students at SD Negeri Merbaun, Kupang Regency. This research method is qualitative, with data collection techniques using observation techniques, interview techniques, data collection techniques using observation techniques, interview techniques, and documentation studies. The data analysis technique used was descriptive qualitative, the number of informants was 6 people consisting of 1 homeroom teacher and 5 students. The results of the data analysis show the type of learning difficulties experienced by fourth-grade students at Merbaun Public Elementary School, Kupang Regency, namely students having difficulty understanding the material. As for the factorts that influence student learning difficulties include (1) learning tools/facilities, (2) laziness and boredom, and (3) low parental support. Efforts can be made to overcome the learning difficulties of fourth-grade students at SD Negeri Merbaun, Kupang Regency, namely (1) the importance of assisting parents in the learning process and (2) creating interesting learning methods and strategies.